Understanding Of Wisdom In The Book Of Daniel - Maiaweng, Peniel C.D. (Jurnal Jaffray, 2016)
Daniel, Hananiah, Misael, and Azariah were young Jewish people who had been taken to Babylon in captivity. They truly obeyed God in their daily life and did not defile themselves with the kingâs food and wine. God honored their decision so He gave them wisdom, that is intellectual ability (knowledge and understanding of all kinds of literature and learning and understanding visions and dreams of all kinds). Their response to the wisdom from God was having a good life style, submitting to God, and carrying burdens. To continue the wisdom from God, they lived in unity, depended on God and had Godâs spirit in them. In doing their job, they spoke with wisdom and tact and worked honestly. In working with the king, they made a courageous decision not to worship the image of god and not to follow the kingâs command. In the kingâs palace, Daniel did not think for himself only, but had a burden to pray for Jerusalem, represent his nation before God, and fast for the future.Â